ERP: Tools, Techniques, and Applications for Integrating the Supply Chain, Second Edition - Ptak, Carol A (CRC Press, 2009)
Completely revised and updated, ERP: Tools, Techniques, and Applications for Integrating the Supply Chain, Second Edition describes, from the perspective of a business manager, concepts and tools for enterprise planning, management, and execution. The text is written in an easy-to-read format, with many real examples from a variety of industries that illustrate key points. This book can be used over and over, as a quick reference to obtain insight into ERP topics.